2010
DOI: 10.1038/nature09138
|View full text |Cite|
|
Sign up to set email alerts
|

Diphthamide biosynthesis requires an organic radical generated by an iron–sulphur enzyme

Abstract: Summary Archaeal and eukaryotic translation elongation factor 2 contain a unique posttranslationally modified histidine residue called “diphthamide”, the target of diphtheria toxin. The biosynthesis of diphthamide were proposed to involve three steps, with the first step being the formation of a C-C bond between the histidine residue and the 3-amino-3-carboxypropyl group of S-adenosylmethionine (SAM). However, details of the biosynthesis have remained unknown. Here we present structural and biochemical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
266
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(273 citation statements)
references
References 44 publications
5
266
0
2
Order By: Relevance
“…Resistance-There are six proteins required for diphthamide biosynthesis: DPH1-5 and WDR85 (10,11,20). Using RT-PCR, we measured the level of the mRNA for each of these proteins and found that the level of WDR85 mRNA was extremely low in CA46-R cells (Fig.…”
Section: Reduced Wdr85 Expression In the Ca46-r Cell Line Is Responsimentioning
confidence: 99%
“…Resistance-There are six proteins required for diphthamide biosynthesis: DPH1-5 and WDR85 (10,11,20). Using RT-PCR, we measured the level of the mRNA for each of these proteins and found that the level of WDR85 mRNA was extremely low in CA46-R cells (Fig.…”
Section: Reduced Wdr85 Expression In the Ca46-r Cell Line Is Responsimentioning
confidence: 99%
“…Diphthamide modification on eukaryotic translation elongation factor 2 (EF2) in budding yeast operates through a multi-step pathway. The diphthamide pathway, modified after Zhang et al (2010), involves known and elusive (?) steps with the intermediates 2-(3-carboxyl-3-aminopropyl)-histidine and diphthine being generated.…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%
“…The second step is a trimethylation reaction to form diphthine, which is catalyzed by a single methyltransferase DPH5. Both the first and second steps have been reconstituted in vitro using purified proteins from a thermophilic archaea, Pyrococcus horikoshii (10)(11)(12). The third step is the amidation of diphthine to form diphthamide.…”
mentioning
confidence: 99%